An analysis of inter-healthcare facility transfer of neonates within the eThekwini health district of KwaZulu-Natal - P. Ashokcoomar*; R. Naidoo (African Journal of Emergency Medicine, 2013)
To assess the time frames for the inter-healthcare facility transfer of neonates and investigate the factors that may have led to delays in the transfer; and investigate any adverse events encountered during the transfer of the neonate. Methods: A prospective study was conducted from December 2011 to January 2012. A quantitative, non-experimental design was used to undertake a descriptive analysis of 120 inter-healthcare facility transfers of neonates within the eThekwini Health District of KwaZulu-Natal. Data collection relied upon two questionnaires. Results: All the transfers were undertaken by road ambulances of which 83 (62.2%) by the operational ambulance units, 35 (29.2%) by the obstetric unit and 2 (1.7%) by the planned patient transport units. Twenty nine (24.2%) were specialised transfers. The mean time ± standard deviation (SD) to complete an inter-healthcare facility transfer was 3 h 49 min ± 1 h 57 min with the minimum time of 5 min and the maximum time of 10 h 34 min. Equipment required for neonatal transport was a major problem due to poor resource allocation, and malfunctioning, inappropriate, insufficient and unsterile equipment. The study identified 10 (8.3%) physiological related adverse events which included 1 (0.8%) death and 18 (15.0%) equipment related adverse events. Conclusions: The EMRS eThekwini Health District is involved in the transportation of a significant number of intensive care and non-intensive care neonates between healthcare facilities. This study has identified numerous factors affecting the efficiency of inter-facility transfer of neonates highlighting various areas requiring improvement.